Funções executivas e atenção: análise em crianças com TDAH com e sem uso do Metilfenidato - Cruz, Lara Fechine Piquet da (2017)
Attention Deficit/Hyperactivity Disorder (ADHD) is a neuropsychological disorder that negatively affects patients' quality of life and affects about 3 to 7% of school-age children. The disorder has as symptomatological triad inattention, hyperactivity and impulsivity and is also related to deficits on executive functions (EF's), attention and verbal fluency. Methylphenidate is the most used psychostimulant in treatment of ADHD and there has been a growing expansion on consumption and prescription of this medication, a fact that may be related to the high consumption also by people who are not diagnosed, but seek cognitive improvement and to the greater amount of this disorder’s diagnoses. This increase in the use of methylphenidate and diagnosis of ADHD, as well as the controversies about the use, benefits and efficacy of the medication and the pressure that children undergo to have a good development on attention and EF's, are factors that lead to the necessity of more studies on ADHD, use of methylphenidate and its relationship with EF's, attention and verbal fluency. From this, the present study was designed in order to analyze the performance on executive functions and attention in children and/or adolescents with ADHD with and without use of methylphenidate. For this, this dissertation presents a first article of systematic review of researches that involve neuropsychological analysis of the performance profile on executive functions and attention of children and/or adolescents with ADHD using methylphenidate. In this, of the 71 publications found between 2010 and 2016, 6 studies were selected that met the inclusion criteria established in two distinct stages. It has been found that the efficacy of methylphenidate is better demonstrated on inhibitory control and cognitive flexibility, but there is a need for further studies regarding the effectiveness of the drug on working memory and attention. The second article of this dissertation is an empirical study that sought to analyze the three main executive functions abilities (working memory, inhibitory control and cognitive flexibility), the sustained, selective and alternated attention and the verbal phonological and semantic fluency of children with ADHD who use methylphenidate. The study included 71 children who were divided into three groups: 38 were part of the control group, 13 were part of the ADHD group with methylphenidate and 20 were part of the ADHD group without methylphenidate. After one-way ANOVA and correspondence analysis have been performed, it was concluded that children with ADHD using methylphenidate presented a lowered profile on executive functions, attention and verbal fluency. Finally, it is observed that there is no unanimity regarding a better or worse performance on executive functions, attention and verbal fluency of children with ADHD who use methylphenidate and stands out the need for new researches of this disorder and the use of methylphenidate, given the importance of knowing more about ADHD and its treatment so that the symptoms and risks caused by the disorder can be minimized and for clarification about the use and effect of the medication.